Specific performance - Masum, Ahmad; Ahmad, Muhamad Hassan; Ali Mohamed, Ashgar Ali; Lilienthal, Gary; Nafees, SMM (CLJ Malaysia Sdn Bhd, 2024)
Specific performance is an equitable remedy. As such, the decision whether or not to grant an order of specific performance is at the discretion of the court in the case of executory contracts.4 The rule governing specific performance in Malaysia is statutorily embodied in the Specific Relief Act 1950.5 The Act contains elaborate provisions governing the remedy of specific performance. The equitable remedy of specific performance in Malaysia is extensively embodied in Chapter II of Part II of the Specific Relief Act 1950. The provisions contained therein specify which contracts may be specifically enforced and which contracts may not be specifically enforced.